2012
DOI: 10.1155/2012/161584
|View full text |Cite
|
Sign up to set email alerts
|

Thirty Years with HIV Infection—Nonprogression Is Still Puzzling: Lessons to Be Learned from Controllers and Long-Term Nonprogressors

Abstract: In the early days of the HIV epidemic, it was observed that a minority of the infected patients did not progress to AIDS or death and maintained stable CD4+ cell counts. As the technique for measuring viral load became available it was evident that some of these nonprogressors in addition to preserved CD4+ cell counts had very low or even undetectable viral replication. They were therefore termed controllers, while those with viral replication were termed long-term nonprogressors (LTNPs). Genetics and virology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 166 publications
(173 reference statements)
2
36
0
3
Order By: Relevance
“…Finally, while progressors were not different from healthy controls, both controllers and LTNP seemed to have reduced amounts of lymphoid tissue in their tonsils in line with earlier findings of HIV damaging lymphoid tissue [1]. Recently damaged lymphoid tissue in the gut was shown in HIV-infected patients, including controllers [43].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Finally, while progressors were not different from healthy controls, both controllers and LTNP seemed to have reduced amounts of lymphoid tissue in their tonsils in line with earlier findings of HIV damaging lymphoid tissue [1]. Recently damaged lymphoid tissue in the gut was shown in HIV-infected patients, including controllers [43].…”
Section: Discussionsupporting
confidence: 80%
“…Another group of non-progressing patients also maintain normal CD4+ T cell counts for several years, but in contrast to controllers these patients have on-going viral replication. This group of patients is therefore termed Long Term Non-Progressors (LTNP) [1]. The mechanism behind the lack of disease progression in LTNP is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of disease progression differs between individuals infected with HIV, and a minority of HIV-infected individuals termed nonprogressors maintain normal CD4 cell counts and do not progress to AIDS or death even in the absence of antiretroviral therapy (ART) [1]. Virological, genetic, and immunological differences between nonprogressors and normal progressors have been described [1].…”
Section: Introductionmentioning
confidence: 99%
“…Virological, genetic, and immunological differences between nonprogressors and normal progressors have been described [1]. However, these parameters do not provide a complete understanding of different rates of disease progression in HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Based on immunological and virological criteria, these long-term survivors (LTS) can be subdivided into long-term nonprogressors (CD4 þ T-cell count >500/ml), elite controllers (undetectable viral load) or viremic controllers (viral load <2000 copies/ml) [6][7][8][9]. Although persistent viremic control most probably results from a combination of not yet fully elucidated mechanisms, several studies reported the importance of host factors, such as the presence of protective human leukocyte antigen (HLA) B57 and B27 major histocompatibility complex (MHC) class I alleles or polymorphisms in CCR5 and CCR2 and a dominant strong virus-specific cytotoxic T-lymphocyte response [10][11][12]. The humoral immune response was considered to play a minor role and was studied mainly for preventive vaccine purposes.…”
mentioning
confidence: 99%